Evaluation Of Village Administration Service Information System To Improve Public Transparency - Siburian, Dian; Zandroto, Irwanndri; Meha, Azun Frinaldi; Aisyah, Nur; Irawan (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Abstract: This study aims to evaluate the effectiveness of the Village Administration Service Information System in enhancing public transparency within village governance. The research employs a qualitative descriptive approach, using literature review and document analysis to examine how information systems support transparency, accountability, and public access to administrative services. The analysis is grounded in information system evaluation models, public transparency theory, and e-government concepts. The results indicate that village administration information systems contribute positively to transparency by improving access to service information, accelerating administrative processes, and strengthening accountability mechanisms. However, several challenges remain, including limited human resource capacity, uneven technological infrastructure, and insufficient policy support. This study highlights the importance of integrating technological readiness, institutional commitment, and human resource development to maximize the role of information systems in fostering transparent village governance. The findings provide a conceptual foundation for future empirical research and policy development related to village digital governance and public transparency.